Prevalence and control of Listeria monocytogenes in the food industry - a review - Imran Khan; Jangrez Khan; Sumaira Miskeen; Charles Nkufi Tango; Youn-Seo Park; Deog-Hwan Oh (Czech Journal of Food Sciences, 2016)
Listeria monocytogenes is a Gram-positive facultative intracellular organism and causative agent of the severe foodborne infection listeriosis. L. monocytogenes is more likely to cause death rather than other pathogenic bacteria that cause foodborne illnesses. It is an ubiquitous organism that can be found in food industry equipment and premises. L. monocytogenes mainly occurs in the food production chain by cross-contamination, making this pathogen a major threat to the food industry. The pathogen may be found at low or moderate levels in the foodstuffs, but the levels involved in listeriosis outbreaks are relatively very high. The majority of isolates from food products belong to serotype 4b and 1/2a. The control of L. monocytogenes can be applied throughout the food chain. Pre- and post-harvest factors such as contact of pigs with pets and pest animals, large group size, hygiene practices, and treatment of manure affected the prevalence of L. monocytogenes in the food chain. Good farm-level practices could be utilised to reduce the occurrence of L. monocytogenes in the farm environment and possibly further in the food chain. Safety and low level of this pathogen in the food chain can be possible with good agricultural practices, good manufacturing practices, and high-quality raw materials. Therefore, food processing plants must be designed carefully with an emphasis on effective cleaning and disinfecting operations in the production line.